2022
DOI: 10.3390/s22103894
|View full text |Cite
|
Sign up to set email alerts
|

Review of Thermal and Physiological Properties of Human Breast Tissue

Abstract: Electromagnetic thermal therapies for cancer treatment, such as microwave hyperthermia, aim to heat up a targeted tumour site to temperatures within 40 and 44 °C. Computational simulations used to investigate such heating systems employ the Pennes’ bioheat equation to model the heat exchange within the tissue, which accounts for several tissue properties: density, specific heat capacity, thermal conductivity, metabolic heat generation rate, and blood perfusion rate. We present a review of these thermal and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 67 publications
(175 reference statements)
0
8
0
Order By: Relevance
“…The calculation was performed with MATLAB with a finite difference time domain (FDTD) method and a Dirichlet boundary condition, such that the initial temperature and the boundary of the breast were kept at a fixed temperature of 37 °C. The thermal properties of the phantom were taken from [ 10 ]. Time was changed into 300 time steps with increments of two seconds, which is the maximum time step ensuring the convergence, completing 10 min of temperature increase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation was performed with MATLAB with a finite difference time domain (FDTD) method and a Dirichlet boundary condition, such that the initial temperature and the boundary of the breast were kept at a fixed temperature of 37 °C. The thermal properties of the phantom were taken from [ 10 ]. Time was changed into 300 time steps with increments of two seconds, which is the maximum time step ensuring the convergence, completing 10 min of temperature increase.…”
Section: Methodsmentioning
confidence: 99%
“…The steps of proper hyperthermia treatment planning (HTP) can be summarized as follows: After the patient is diagnosed with a malignant tumor, detailed imaging of the body part is obtained and the tissues are segmented [ 4 , 5 ]. Next, the accurate microwave dielectric and thermal properties of the tissues are assigned to each tissue type [ 6 , 7 , 8 , 9 , 10 ]. Then, the proper antenna excitations are applied for a controlled increase of the tumor temperature and hotspot prevention in the remaining healthy tissue, in other words the effective focusing of the specific absorption rate ( ) on the target.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging the thermal properties (TPs) of human tissues, such as blood perfusion parameters and thermal conductivity, is helpful for tumor diagnosis and treatment. Images of TPs can assist in the diagnosis of breast tumors, because breast tumors and healthy breast tissues have different TPs (Duck 2013, Lozano et al 2020, Said Camilleri et al 2022. In particular, the blood perfusion rate is significantly different for cancerous and healthy breast tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted at several medical, pharmaceutical, and technical universities concluded that the influence of mobile phones leads to eye strain, lack of sleep, migraines, restlessness, and irritability and may cause hearing impairment. Radiation from mobile phones and their effect has been found to have a greater effect on people under 20 years of age [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%